Faktor Risiko dan Perbandingan Stres Akademik Mahasiswa Baru Sebelum dan Sesudah COVID-19 - Evangeline Deborah; Aria Saloka Immanuel (CV. ITTC INDONESIA, 2024)
This literature review aims to identify risk factors that affect academic stress in new students, as well as find out a comparison of stress levels before and after the COVID-19 pandemic. Through the online database Science Direct, Google Scholar, and EBSCO, the search starts from September to December 2022. Based on the results of the analysis, it was found that there are several risk factors that make new students especially experience academic stress. before the COVID-19 pandemic in the form of social support and self-efficacy, good parent-child communication, self-adjustment, the way lecturers teach, lecture schedules, relationships with friends, and the gender of women who are vulnerable to academic stress. While the risk factors after COVID-19 are resilience and social support, peer support, adjustment, possibility of transmission of COVID-19, difficulty understanding lecture material, limited activities and boredom while staying at home, and adjustment. The different factors that influenced the increase in academic stress before the pandemic were in the form of social support and self-efficacy, parent-child communication, self-adjustment, teaching methods, class schedules, relationships with friends, and women. Meanwhile, factors that influence post-pandemic academic stress increase include resilience and social support, peer support, self-adjustment, vulnerability to COVID-19 transmission, difficulty understanding lecture material, activity restrictions and boredom while staying at home, and self-adjustment.